Establishing a Novel E. coli Heterologous Secretion Expression System Mediated by mScarlet3 for the Expression of a Novel Lipolytic Enzyme - Jun Yang; Mingjun Yang; Huichen Liu; Xinyu Liu; Fei Wang; Wenqiang Li; Yang Liu; Chao Zhai; Lixin Ma (Biomolecules)
Our previous study demonstrated that an Escherichia coli heterologous secretion expression system, mediated by superfolder green fluorescent protein (sfGFP) mutants, significantly enhances recombinant lipase yield and reduces large-scale production costs. In this study, we identified mScarlet3, a fast-folding fluorescent protein, as another effective mediator of secretion expression in E. coli. A novel lipolytic enzyme, named LipHu6, was identified through sequence alignment. Secretion expression of LipHu6 was achieved by fusing mScarlet3 to either its N- or C-terminus. The specific activity of mScarlet3-LipHu6 reached 669,151.75 U/mmol, slightly surpassing that of LipHu6 alone (646,682.69 U/mmol) and markedly exceeding that of sfGFP(-15)-LipHu6 (492,432.39 U/mmol). Notably, N-terminal mScarlet3 fusion had no impact on LipHu6 hydrolytic activity toward short-chain p-nitrophenyl fatty acyl esters (C2–C8). In contrast, mScarlet3-LipHu6 exhibited approximately 1.5- and 1.7-fold increases in hydrolytic activity toward p-nitrophenyl palmitate (p-NPP, C16) and p-nitrophenyl stearate (p-NPS, C18), respectively. In conclusion, this study establishes a novel E. coli heterologous secretion expression system mediated by mScarlet3, offering a highly efficient and cost-effective strategy for the large-scale production of lipolytic enzymes.